Menganalisis Struktur Batin dan Struktur Fisik Puisi “SEBUAH JAKET BERLUMUR DARAH” Karya Taufiq Ismail - Annisa Al Dhira Jahra; Hana Ghina Hanifah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research was motivated by the researcher's curiosity about the poetry of Taufiq Ismail, he is known as a poet of demonstration poetry. The poem with the title